2020
DOI: 10.1186/s12891-020-03480-2
|View full text |Cite
|
Sign up to set email alerts
|

Weight control in older adults with knee osteoarthritis: a qualitative study

Abstract: Background: Knee osteoarthritis (OA) affects mostly older adults and its primary risk factor is obesity. This study sought to understand weight-control strategies, facilitators of and barriers toward weight control in older adults with knee OA who preferred not to undergo physician-recommended total knee arthroplasty. Methods: For this qualitative descriptive study, older outpatients (N = 118) were recruited from orthopedic clinics at three hospitals. Data were collected through face-to face, individual in-dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 28 publications
0
34
0
1
Order By: Relevance
“…Pain and sleep are also determinants of quality of life, and both are associated with obesity and aging. In addition, pain is a barrier to performing everyday activities and losing body weight 107,110 . The number of medications taken is high in older people with obesity 111 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pain and sleep are also determinants of quality of life, and both are associated with obesity and aging. In addition, pain is a barrier to performing everyday activities and losing body weight 107,110 . The number of medications taken is high in older people with obesity 111 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, pain is a barrier to performing everyday activities and losing body weight. 107,110 The number of medications taken is high in older people with obesity. 111 In diabetic adults with overweight and obesity, it has been shown that body weight loss is associated with a reduction in antidiabetic and antihypertensive drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Despite their effectiveness, ketogenic VLCDs are underutilised 25e27 , and, to our knowledge, no previous studies have investigated their effectiveness in people with OA or other chronic musculoskeletal conditions. Such an intensive and restrictive diet may be perceived as onerous and difficult, particularly given that people with OA believe controlling appetite and diet is difficult and uncomfortable 28 and that exercise is more important than dietary change for weight management 14 . No previous studies have explored the perceived acceptability of an intensive dietary weight loss program amongst people with OA or dietitians.…”
Section: Introductionmentioning
confidence: 99%
“…27 In terms of weight concern, it may be important to educate patients about healthy eating. 28 Patients undergoing an orthopaedic surgical procedure are often day cases, placing extensive responsibility to recover at home. Patients have expressed that better information about pain management would be helpful and should be delivered at multiple time points.…”
Section: Discussionmentioning
confidence: 99%